2013
DOI: 10.1158/2159-8290.cd-12-0558
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the MET Receptor Drives Resistance to Anti-EGFR Therapies in Colorectal Cancer

Abstract: EGFR targeted monoclonal antibodies are effective in a subset of metastatic colorectal tumors (mCRC). Inevitably, all patients develop resistance, which occurs through emergence of KRAS mutations in approximately 50% of the cases. We show that amplification of the MET proto-oncogene is associated with acquired resistance in patients who do not develop KRAS mutations during anti-EGFR therapy. Amplification of the MET locus was present in circulating tumor DNA before relapse was clinically evident. Functional st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
488
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 595 publications
(515 citation statements)
references
References 51 publications
23
488
0
4
Order By: Relevance
“…We previously reported that a subset of colorectal tumours, in which resistance to EGFR blockade occurs in a RAS/RAF wildtype background, display overexpression of two TK genes, HER2 or MET 33,34 . In 41/151 lines, which were analysed in this study, the mechanism of resistance to cetuximab is unaccounted for.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a subset of colorectal tumours, in which resistance to EGFR blockade occurs in a RAS/RAF wildtype background, display overexpression of two TK genes, HER2 or MET 33,34 . In 41/151 lines, which were analysed in this study, the mechanism of resistance to cetuximab is unaccounted for.…”
Section: Discussionmentioning
confidence: 99%
“…31 MET amplification was also the cause of resistance for colorectal cancer patients treated with anti-EGFR antibody therapy. 32 These observations underlie the key role of EGFR and MET in promoting resilient tumor growth and it will be interesting to check whether EPAS1 also plays similar role in other types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…De manière générale, la surexpression de l'HGF/SF ou de Met est de mauvais pronostic. Un dernier élément, et non le moindre dans le contexte des thérapies anticancéreuses, réside dans les résis-tances aux thérapies ciblant l'EGFR (epidermal growth factor receptor) dans les cancers du poumon et du côlon que caractérise une surexpression de Met [37,38]. L'activation de Met permet alors de compenser l'inhibition de l'EGFR, et ceci de manière d'autant plus efficace que les réseaux de signalisation des deux récepteurs à activité tyrosine kinase sont très similaires.…”
Section: Mise En éVidence Des Dérégulations Du Couple Hgf/sf-met Dansunclassified
“…Many questions still remain unanswered such as the involvement of Met in several processes of development, the mechanisms involving Met in resistance to current therapies or the likely emergence of resistances to Mettargeted therapies. ‡ du poumon ou colorectaux [37,38] 1987 : découverte du SF [3] 1991 : l'HGF et le SF sont un même ligand et Met est leur récepteur [4] 2003 : résolution de la structure de Met [6,7] 1994 : Met recrute les protéines de signalisation par un site de recrutement multi-substrat 1995 : le couple HGF/SF-Met est nécessaire au développement embryonnaire [10][11][12] 2001 : Met est ubiquitiné par Cbl en réponse à l'HGF, ce qui induit sa dégradation [20] 2004 : Met est un récepteur à dépendance qui favorise l'apoptose suite à son clivage par les caspases [22] 2008 : l'internalisation de Met participe aussi à sa signalisation [24] 2009-2012 : Met est régulé également par des mécanismes de type PS-RIP [23] 2005 : début des essais cliniques avec des TKI ciblant Met…”
Section: Perspectivesunclassified